Kahoot! and quizlet as a scaffolding strategy enhance english language vocabulary among ketpreparation students at english speak up center, afternoon session in the Loja city during 2020–2021 school year - Torres Maita, David Andrés (2021)
The objective of this research work was to enhance the English language vocabulary through the application of Kahoot! and Quizlet as a scaffolding strategy among Ketpreparation students at English Speak Up Center, afternoon session in the Loja city during the 2020-2021 school year. The methods required were the scientific method, descriptive, analytic-synthetic, and the statistic method which were employed to describe, process, analyze and interpret the data. Tests and questionaries were applied to four students to obtain the data about vocabulary. Field notes and observation sheets were used to record information about students’ attitudes. Kahoot! and Quizlet as a scaffolding strategy enhanced meaningfully students’ English vocabulary in four aspects related to: meaning, spelling, antonyms, and idioms. Students’ participation increased as well as their grades. They become more competent in the use of a wide range of the English vocabulary